The Influence of High Performance Work Systems on Service Quality and the Mediating Role of Trust, Job Satisfaction and Affective Commitment - Ramadhan, Eza Anugerah; Fajarwati, Diana (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This research aims to prove the existence of a relationship between all variables that are assumed to occur in Beauty Clinics in the DKI Jakarta area, consisting of the variables High Performance Work System (HPWS), Trust, Job Satisfaction, Affective Commitment and Service Quality. The research approach used in this research is quantitative research. The population in this study were employees who worked in the Beauty Clinic industry in the DKI Jakarta area. The data was collected using a survey method by distributing questionnaires to respondents, namely Beauty Clinic employees in the DKI Jakarta area with a work period of more than 1 year. The questionnaires collected were 210 respondents, the data was then processed using Smart PLS. Partially, theHigh Performance Work System (HPWS) variable has been proven to have a positive effect on Trust, Job Satisfaction and Affective Commitment. Then Trust, Job Satisfaction and Affective commitment have a positive effect on Service Quality. Furthermore, results were obtained regarding the mediating role of Trust, Job Satisfaction and Affective Commitment on the influence of theHigh Performance Work System on Service Quality. Keywords: high performance work system. trust, job satisfaction, affective commitment, service quality